EMOTIONAL INVENTORY OF MATHEMATICS TEACHERS AT MADRASAH IBTIDAIYAH - Siska Merrydian; Khaerun Nisa; Iva Sarifah; Gaguk Margono (Adisam Publisher, 2025)
Although there is an increasing amount of research on assessing teacher emotions in general education, there is still a lack of appropriate measurement tools to measure mathematics teachers' emotions. The aim of this research is to develop an instrument for mathematics teachers' emotions and produce a ready-to-use instrument. The analytical method used is Confirmatory Factor Analysis (CFA). The sample used consisted of 310 mathematics teachers. The sample involved teachers from several madrasah ibtidaiyah in DKI Jakarta. Confirmatory Factor Analysis produces 5 factors, namely, Love, Joy, Anger, Sadness and Fear which produces 29 fit items. Thus, this assessment instrument is valid and reliable for use as a measuring tool for mathematics teachers' emotions.